Mild Homogeneous Synthesis of Gold Nanoparticles through the Epoxide Route: Kinetics, Mechanisms, and Related One-Pot Composites - Oestreicher, Víctor Santiago Jesús; Huck Iriart, Cristián; Soler Illia, Galo Juan de Avila Arturo; Angelome, Paula Cecilia; Jobbagy, Matias (Wiley VCH Verlag, 2020)
Fil: Oestreicher, Víctor Santiago Jesús. Universidad Nacional de San Martin. Instituto de Nanosistemas; Argentina. Comisión Nacional de Energía Atómica. Unidad Ejecutora Instituto de Nanociencia y Nanotecnología. - Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad Ejecutora Instituto de Nanociencia y Nanotecnología; Argentina